Introducing tobacco : risks, laws and habits [ - VEA Australia (Australia : VEA Australia Pty Ltd, 2007)
For over 50 years now we have known that smokingkills - yet millions of people continue to court disease and death. Why? Tabacco is big business - insidious, wily and determined to hook the vulnerable, and to obscure the devastating effects of their deadly merchandise. This program delivers the facts about tobacco smoking and the effects it has on both users and non-users. Featuring international experts and a dramatised story of a young girl who loses her father to lung cancer, this program is a sobering, informative and persuasive program that addresses the root causes, laws, and short and long-term effects of this killer product. A thought-provoking discussion starter for students.
Program support notes available on www.VEA.com.au
English captions for the deaf and hearing impaired.
Keywords: Smoking -- adverse effects; Tobacco -- adverse effects; Tobacco Use Disorder